(untitled) (Fiep Bulletin - online, 2015)
Recently, the interest in the relationship between muscle size and strength has been revived. The writings of Hettinger indicate that he considers the strength (per unit area of physiological cross section) to be constant at 4 kg/cm2. In other words, “it is the actual size of the muscle which determines its strength.